2011
DOI: 10.1519/jsc.0b013e3182132ce7
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Carminatti's Test to Determine Physiological Indices of Aerobic Power and Capacity in Soccer and Futsal Players

Abstract: The aim of this study was to verify the validity of a new progressive distance and fixed time test (Carminatti's test [TCAR]) in estimating the main physiological indices of aerobic fitness in team-sport players. Thirty professional national level team-sport players (n = 12 futsal players and 18 soccer players) volunteered to participate in this study. The subjects performed the TCAR and a laboratory incremental treadmill test (ITT). The TCAR required subjects to complete repeated sets of 5 × 12-second shuttle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
13

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(74 citation statements)
references
References 24 publications
3
58
0
13
Order By: Relevance
“…The HrDP is often found at intensities close to the LT [15]. Accordingly, our results corroborate the observations by Conde et al [16] and Dittrich et al [13], who found the HrDP at 91.8 ± 3.9 %Hr max and 91.6 %Hr max , respectively, whilst we established it at 89.7 ± 4 %Hr max .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The HrDP is often found at intensities close to the LT [15]. Accordingly, our results corroborate the observations by Conde et al [16] and Dittrich et al [13], who found the HrDP at 91.8 ± 3.9 %Hr max and 91.6 %Hr max , respectively, whilst we established it at 89.7 ± 4 %Hr max .…”
Section: Discussionsupporting
confidence: 93%
“…Dittrich et al [13] found the HrDP in all individuals submitted to an intermittent field test in which the velocity increased linearly (Carminatti's Test, TCar). In the present study, however, the HrDP could not be assessed in subjects whose Hr values equal or higher than 140 beats · min -1 were achieved at intensities lower than 13 km · h -1 .…”
Section: Discussionmentioning
confidence: 99%
“…Já atletas de basquetebol percorrem em torno de 4000-5000 metros, média de frequência cardíaca de 171 batidas por minuto (bpm), sendo 18% do tempo em atividades de elevada intensidade (KARCHER e BUCHHEIT, 2014), enquanto que os atletas de futebol percorrem em média 10 km em uma intensidade próxima ao limiar anaeróbio ou 80-90% da frequência cardíaca máxima (HELGERUD et al, 2001), porém, apenas 10% percorridos em níveis considerados intensos (McMILLAN et al, 2005). Segundo Da Silva et al, (2011) o PVT-CAR está associado com índices aeróbios (VO2Máx, máxima velocidade aeróbia e LL), como a velocidade correspondente ao ponto de deflexão da frequência cardíaca pelo método visual (VPDFC) e a porcentagem fixa de 80,4% do PV (V80.4), bem como medidas padrão realizadas em laboratório (DITTRICH et al, 2011). As principais vantagens dos testes de campo, são que estes disponibilizam dados de PV, que segundo Noakes (1988), representa uma medida integradora da performance aeróbia, além de ser um índice de fácil determinação, sem a necessidade de técnicas invasivas, equipamentos sofisticados, com baixo custo e maior especificidade.…”
Section: Discussionunclassified
“…O ritmo é ditado por um sinal sonoro (bip), em intervalos regulares de 6 segundos, na qual determina a velocidade de corrida a ser desenvolvida nos deslocamentos entre as linhas paralelas demarcadas no solo e também sinalizadas por cones. A velocidade inicial do teste é de 9,0 km.h (distância inicial de 15 m) com incrementos de 0,6 km.h a cada estágio, até a exaustão voluntária, mediante aumentos sucessivos de 1m a partir da distância inicial (CARMINATTI; LIMA-SIL-VA; DE OLIVEIRA, 2004;DITTRICH et al, 2011). Durante o teste cada atleta utilizou um cardiofrequencímetro marca Polar (Electro®-modelo S610), armazenadas em intervalos de 5 segundos.…”
Section: Materiais E Métodosunclassified
See 1 more Smart Citation